Sistem Pendukung Keputusan Pemilihan Pegawai Pemerintah Non Pegawai Negeri (PPNPN) Terbaik Pada Kantor Imigrasi Kelas I Polonia Medan Menerapkan Metode Multifactor Evaluation Process (MFEP) - Muhammad Wirza Pratama Agatmadja; Surya Darma Nasution (STMIK Budi Darma, 2020)
The decision making process for the selection of the best non-civil servant government employees is still done manually, where in the election there are still often some non-civil servant government employees (ppnpn) that are not appropriate as desired by the agency, so that in the election there are still nonconformities with existing procedures, therefore the need for a decision support system that will later assist in the decision making process. Decision support system is a system that can be used to support decision makers with the best alternative in making decisions in the process of selecting non-civil servant government employees (PPNPN) at the Polonia Class I Immigration Office. The Multifactor Evaluation Process (MFEP) method is a fairly simple method that can be used in decision making to analyze multiple criteria. This method will make decisions with several criteria that conflict with each other and will produce the greatest value that will be selected as the best alternative. The results of the calculation of this method will be as expected if the chosen alternative meets the specified criteria. Thus a decision support system is needed so that it can help make the right decision in the selection of the best non civil servant government employees (PPNPN) at the Polonia Class I Immigration Office. In a decision support system there are several methods that can be used to solve a problem in making a decision